AUDIT INTERNAL DALAM PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 DI SMK MUHAMMADIYAH 1 WONOSOBO (JPP, 2011)
To the effect this research is subject to be find: (1 ) phase are in contemplation, (2 ) preparations(3 ) performing and reporting trick, (4 ) performing trick audit follow-ups inSMM ISO 9001:2008. In this research one will be observed is person, which is QMR /WMM and Team ISO in particular internal auditing activity in implemented SMM ISO9001:2008 by various its activity. Finding in observational it as, planning first internalauditing which is: was optimal deep determines all standard element that shall be auditted,secondly preparation internal auditing which is: auditors not all have grasp depththat adequately as auditor, one that drd internal auditing performing which is: internalauditing can do schedule outboard, and fourthly which is: KTS that found up to internalauditing therefore follow-up audit performed by auditors to check and ensures repair action/ correction action be done by job unit chairman. In this research suggests a fewthings, which is (1 ) SMM'S understanding qualities ISO 9001:2008 shall ever be increased.(2 ) a uditor shall have grasp to SMM ISO 9001:2008 so not experience doubtsin do internal auditing, (3 ) internal auditing Auditors shall understand six mandatoryclauses in SMM ISO 9001:2008, (4 ) need to be performed by next internal auditing researches.Keyword : quality management system (SMM),quality management representative(WMM)